2016
DOI: 10.1111/peps.12206
|View full text |Cite
|
Sign up to set email alerts
|

Worked to Death: The Relationships of Job Demands and Job Control with Mortality

Abstract: Despite recent calls in the literature to examine the effects of the occupational context on physiological outcomes, such as mortality, little research has accumulated on this front. Thus, the purpose of this study is to investigate the interactive relationship between job demands, control, and death. Drawing from the job design, stress, and epidemiology literatures, we argue that job demands will be positively related to mortality under conditions of low control, and negatively related to mortality under cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 108 publications
(208 reference statements)
2
64
0
1
Order By: Relevance
“…Alternatively, when demands are high and decision authority is high, workers can make decisions about how to manage demands, for example, by spacing demands or by taking time away from demands (Häusser et al ., ). Longitudinal study and objective measurement have supported this notion (de Jonge, van Vegchel, Shimazu, Schaufeli, & Dormann, ; Gonzalez‐Mulé & Cockburn, ). Using specific job demands (e.g., emotional demands, physical demands) and job resources (i.e., decision authority), de Jonge et al .…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, when demands are high and decision authority is high, workers can make decisions about how to manage demands, for example, by spacing demands or by taking time away from demands (Häusser et al ., ). Longitudinal study and objective measurement have supported this notion (de Jonge, van Vegchel, Shimazu, Schaufeli, & Dormann, ; Gonzalez‐Mulé & Cockburn, ). Using specific job demands (e.g., emotional demands, physical demands) and job resources (i.e., decision authority), de Jonge et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the fields of work environment and work psychology, job control is often defined and operationalized as the social authority over decision-making in relation to work tasks (Häusser et al 2010;Karasek & Theorell 1990;Van der Doef & Maes 1999). The work of Karasek and Theorell (1990) has been especially central to discussions of job control in relation to occupational health and well-being, and although other approaches such as the job demands-resources model (Bakker & Demerouti 2007) have since gained prominence, the conceptualization of job control suggested by Karasek and Theorell is still used today (e.g., Aronsson et al 2019;Fritz & Knippenberg 2019;Gonzalez-Mulé & Cockburn 2017) With inspiration from the work of Karasek and Theorell, job control is typically approached in the POLI literature at the individual level as something employees perceive (e.g., Bourbonnais 2006;Hätinen et al 2007;Landsbergis & Vivona-Vaughan 1995;Mikkelsen et al 2000). When employees' perceived job control changes during the intervention process (as measured by questionnaire data, for example), the change is typically attributed to the intervention, suggesting that the perception is otherwise thought to be stable.…”
Section: Participatory Organizational-level Interventions and Job Conmentioning
confidence: 99%
“…7 Black men in the labor force are more likely than men from other ethnic groups to work in low-complexity work environments and be exposed to increased work stressors including shift work, low control and high demands, poor-tono health insurance, longer hours, and job insecurity -which are predictors for increased work-related stressors 3 and a 15.4% increase in mortality. 8 Kivimaki and colleagues found that men diagnosed with cardiometabolic disease (presence of coronary heart disease, stroke, or diabetes) and who worked in environments exposed to job strain had higher mortality risk rates than those in work environments with no job strain. These mortality risk rates were comparable to rates for men who were smokers but higher than the mortality risk rates of men who had been physically inactive or diagnosed with hypertension, obesity, and high alcohol use.…”
Section: Work-related Stress and Mortality In Black Menmentioning
confidence: 99%
“…On an average day, most US workers em-ployed fulltime (84.1%) spend more awake time in the work environment than in the home environment -Black men aged <16 years spend an average of 42.6 hours weekly in the work environment. 8 Given the cumulative amount of lifetime hours spent at work, the influence of work on the mortality risk rates of Black men may be particularly important.…”
Section: Need For Research On Life Course Influences Of Work-related mentioning
confidence: 99%